Re-irradiation of the chest wall for local breast cancer recurrence : Results of salvage brachytherapy with hyperthermia - Auoragh, A.; Strnad, Vratislav; Ott, O. J.; Beckmann, Matthias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
Following mastectomy and adjuvant external beam radiation therapy in patients with breast cancer, the incidence of local or locoregional recurrence is approximately 9 % (2-20 %). Alongside the often limited possibilities of surgical treatment, radiation therapy combined with superficial hyperthermia is the most effective local therapy. In the present work, a retrospective analysis of salvage brachytherapy combined with superficial hyperthermia for chest wall recurrences is presented.Between 2004 and 2011, 18 patients with a total of 23 target volumes resulting from chest wall recurrences after previously mastectomy and external beam radiation therapy (median 56 Gy, range 50-68 Gy) were treated with superficial brachytherapy as salvage treatment: 8 patients (44 %) had macroscopic tumor, 3 (17 %) had microscopic tumor (R1), and 7 (39 %) had undergone R0 resection and were treated due to risk factors. A dose of 50 Gy was given (high-dose rate [HDR] and pulsed-dose rate [PDR] procedures). In all, 5 of 23 patients (22 %) received additional concurrent chemotherapy, and in 20 of 23 (87 %) target volumes additional superficial hyperthermia was carried out twice weekly.The 5-year local recurrence-free survival was 56 %, the disease-free survival was 28 %, and a 5-year overall survival was 22 %. Late side effects Common Toxicity Criteria (CTC) grade 3 were reported in 17 % of the patients: 2 of 18 (11 %) had CTC grade 3 fibrosis, and 1 of 18 (6 %) had a chronic wound healing disorder.Re-irradiation as salvage brachytherapy with superficial hyperthermia for chest wall recurrences is a feasible and safe treatment with good local control results and acceptable late side effects.
EVALuna2:18364